Differences Between Single and Double Eyelid Anatomy in Asians Using Ultrasound Biomicroscopy. Issue 5 (September 2016) - Saonanon, Preamjit; Thongtong, Penake; Wongwuticomjon, Tee
Abstract : Purpose: The aim of this study was to clarify the differences between single and double eyelid structures quantitatively using an ultrasound biomicroscopy. Design: A single-center observational study. Methods: Upper eyelids of Asian volunteers were evaluated with a 50-MHz ultrasound biomicroscopy. The skin–orbicularis oculi complex (SOOC), levator aponeurosis, Mueller muscle–conjunctival complex, and tarsus were imaged at the eyelid crease in the double eyelid group and 7 mm above the eyelid margin in the single eyelid group. The SOOC was also measured 2 mm above the eyelid margin and 5 mm above the eyelid crease. Results: Forty-two upper eyelids of 42 subjects were studied. Mean SOOC thickness at the eyelid crease was 0.62 ± 0.12 mm in single eyelids and 0.57 ± 0.08 mm in double eyelids ( P = 0.03). Mean SOOC thickness at 2 mm above the eyelid margin and 5 mm above the crease was not significantly different between single and double eyelids ( P = 0.004 and P = 0.62, respectively). The levator aponeurosis, Mueller muscle–conjunctival complex, and tarsus measured 0.38 ± 0.12 mm, 0.86 ± 0.28 mm, and 10.84 ± 1.10 mm in single eyelids and 0.39 ± 0.14 mm, 0.88 ± 0.34 mm, and 10.61 ± 1.36 mm in double eyelids ( P = 0.75, P = 0.81, and P = 0.54, respectively). Conclusions: Single eyelids showed slightly thicker SOOC in the pre-tarsal area and at the eyelid crease but not 5 mm above the eyelid crease. The levator aponeurosis, Mueller muscle–conjunctival complex, and tarsus showed no differences in thickness.